Immunocorrective therapy of patients with purulent-inflammatory diseases of the soft tissues of the maxillofacial area and neck - Тимофеев, Алексей Александрович; Блинова, Виктория Павловна; Умиров, Александр Владимирович; Мирошник, Антон Александрович; Ухарская, Оксана Анатольевна; Дубиченко, Сергей Игоревич; Серга, Елена Александровна (Actual Dentistry, 2019)
Purpose: determine the effectiveness of using the drug «Biotroph» on the state of local and general nonspecific resistance of the organism in patients with purulent-inflammatory diseases of the soft tissues of the maxillofacial area and neck. Methods. Сlinical and immunological examination of 132 patients with limited and diffuse purulent-inflammatory maxillofacial and neck area soft tissues diseases identified during hospitalization was carried out. Results. Our studies have shown that the using of food supplements «Biotroph-4» in the complex treatment of the patients with limited and diffuse purulent-inflammatory maxillofacial and neck area soft tissues diseases allowed eliminate the temporary immunodeficiency completely in the short period of time in all examined patients. Conclusions. The complex drug on a natural basis «Biotroph-4» is recommended to maxillofacial surgeons and dental surgeons for the treatment of patients with purulent-inflammatory diseases of periomaxillary soft tissues. Key words: abscesses, phlegmons, purulent lymphadenitis, boils, carbuncles, treatment, immunity, immunodeficiency, biotroph.